Relations Between Stress Level and the Occurrence of Constipation to Medical Students - Arsita, Elli; Wician, Fendra; Mamudi, Chrispian Oktafbipian; Mahonny, Glorie Libertikha (Jurnal MedScientiae, 2024)
Stress can be experienced by anyone. The number of events is increasing every year. This isevidenced from the results of Basic Health Research in 2013 and 2018, namely an increase in theprevalence of mental emotional disorders in Indonesian population aged ≥ 15 years from 6percent to 9.8 percent. Stress can have a negative impact on the human body both physically andpsychologically. One of the effects of stress on the body is constipation. Unfortunately not muchliterature discusses stress and constipation in more detail. This study aims to determine whetherthere is a relationship between stress levels and constipation in the seventh semester students ofthe 2016 Faculty of Medicine and Health Sciences at Ukrida. This research uses analytic studymethod with cross-sectional approach. Sampling is done by consecutive sampling method. Thestudy was conducted in December 2019 at the Ukrida’s medical campus. 150 out of 206 studentsof 2016 from Ukrida Faculty of Medicine and Health Sciences who are in their seventh semester,are included in the inclusion criteria. The research material is primary data in the form of aConstipation Scoring System questionnaire and Perceived Stress Scale. The results showed arelationship between stress levels and constipation. This was obtained from the Chi Square testcalculation which was calculated using the SPSS computer program, where the p value was 0.01(p <0.05).